2021
DOI: 10.1136/bmjopen-2020-045343
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on utilisation of healthcare services: a systematic review

Abstract: ObjectivesTo determine the extent and nature of changes in utilisation of healthcare services during COVID-19 pandemic.DesignSystematic review.EligibilityEligible studies compared utilisation of services during COVID-19 pandemic to at least one comparable period in prior years. Services included visits, admissions, diagnostics and therapeutics. Studies were excluded if from single centres or studied only patients with COVID-19.Data sourcesPubMed, Embase, Cochrane COVID-19 Study Register and preprints were sear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
718
5
18

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 921 publications
(905 citation statements)
references
References 31 publications
47
718
5
18
Order By: Relevance
“…This increase since pre-pandemic levels also suggests that lack of access to healthcare following the second wave is less of a problem than in wave one; however, evidence indicates this can nevertheless still be difficult. 16,19 Contrary to our findings however, a Norwegian study suggested that mild COVID-19 does not persist to cause a need for healthcare beyond two months following a positive test. 22 It is unclear if symptoms or diseases post-COVID-19 are due to the infection itself, anxiety caused by diagnosis and isolation or due to complications.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This increase since pre-pandemic levels also suggests that lack of access to healthcare following the second wave is less of a problem than in wave one; however, evidence indicates this can nevertheless still be difficult. 16,19 Contrary to our findings however, a Norwegian study suggested that mild COVID-19 does not persist to cause a need for healthcare beyond two months following a positive test. 22 It is unclear if symptoms or diseases post-COVID-19 are due to the infection itself, anxiety caused by diagnosis and isolation or due to complications.…”
Section: Discussioncontrasting
confidence: 99%
“…This was important as changes in healthcare utilisation during the pandemic have been recognised and may influence outcome events. 19 Baseline characteristics included the most recent measurement of body mass index (BMI) within five years of index date. Smoking status and the Charlson Comorbidity Index (CCI) were identified at any time point before COVID-19 diagnosis.…”
Section: Study Populationmentioning
confidence: 99%
“…During Ebola, weekly admissions decreased by 51%(16), compared to decreases of 14.7% (Q1-Q2) and 13.2% (Q1-Q3) in this study. The decreases are also lower than the median decrease in admissions of 28.4% (17.4-40.4) from 43 studies in a recent worldwide systematic review(4). We observed similar patterns of change in healthcare utilisation to those found during Ebola.…”
Section: Discussionmentioning
confidence: 59%
“…Thus far, there has been limited research on the impact of COVID-19 on essential health services in sSA, including Sierra Leone. A systematic review published in 2021, of the impact of COVID-19 on healthcare utilisation worldwide, found no eligible studies from sSA and only four studies from non-African Low and Middle Income countries (LMICs)(4). In rural South Africa, a single centre interrupted time series analysis, found no significant change in total admissions during 2020, but did find significant changes between subgroups of admissions(5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation